2017
DOI: 10.3390/w9050339
|View full text |Cite
|
Sign up to set email alerts
|

Water Bridging Dynamics of Polymerase Chain Reaction in the Gauge Theory Paradigm of Quantum Fields

Abstract: We discuss the role of water bridging the DNA-enzyme interaction by resorting to recent results showing that London dispersion forces between delocalized electrons of base pairs of DNA are responsible for the formation of dipole modes that can be recognized by Taq polymerase. We describe the dynamic origin of the high efficiency and precise targeting of Taq activity in PCR. The spatiotemporal distribution of interaction couplings, frequencies, amplitudes, and phase modulations comprise a pattern of fields whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In this respect, some innovative papers with designed and properly controlled experiments, suggested that electromagnetic fields may reflect macromolecular features of enzymes like DNA-polymerase in water, and that this provides structure specific information storage in aqueous solutions [82] [83] [84]. The electromagnetic radiative properties of DNA and enzyme macromolecules likely depend on the characterization of their electric dipoles.…”
Section: The Essential Role Of Cell Water In the Protein Folding Procmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, some innovative papers with designed and properly controlled experiments, suggested that electromagnetic fields may reflect macromolecular features of enzymes like DNA-polymerase in water, and that this provides structure specific information storage in aqueous solutions [82] [83] [84]. The electromagnetic radiative properties of DNA and enzyme macromolecules likely depend on the characterization of their electric dipoles.…”
Section: The Essential Role Of Cell Water In the Protein Folding Procmentioning
confidence: 99%
“…It has been argued that London force dipoles in such intra-protein hydrophobic pockets could couple together and oscillate coherently, thus generating a radiative field. Montagnier recently described the fundamental role of water dipole dynamics bridging the interaction between DNA and enzymatic proteins (see Figure 7) so as to allow polymerase chain reaction (PCR) processes to occur [84]. They describe the dynamic origin of the high efficiency and precise targeting of Taq activity in PCR.…”
Section: The Essential Role Of Cell Water In the Protein Folding Procmentioning
confidence: 99%
“…The authors wish to make the following addendum to their paper [1]: After the publication of our paper, submitted on 11 February 2017, we read the paper "DNA's Chiral Spine of Hydration", by M. Luke McDermott, Heather Vanselous, Steven A. Corcelli, and Poul B. Petersen, published in ACS Central Science, doi:10.1021/acscentsci.7b00100, on 24 May 2017 [2], where the authors report their discovery of a chiral water superstructure surrounding DNA under ambient conditions. This is the first observation of a chiral spine of hydration templated by a biomolecule and has been obtained by use of chiral sum frequency generation (SFG) spectroscopy, a method analogous to circular dichroism measurements.…”
mentioning
confidence: 99%
“…As all biomolecules in real biological environment are in watery solution, we have to take into account the presence of surrounding water molecules. Though recent studies reveal that the water in biological system can have a highly non trivial behaviour with respect to electrodynamic fields generated by the electric dipole of biomolecules [12][13][14][15][16], in this article we will assume the surrounding water to play simply the role of a thermal bath.…”
Section: A Biological Watery Environment As Thermal Bathmentioning
confidence: 99%